Prussian Blue analogs and transition metal K-edge XMCD: a longstanding friendship - Bordage, Amélie; N’Diaye, Adama; Bleuzen, Anne (Comptes Rendus. Chimie)
Prussian Blue analogs (PBAs) are well-known coordination polymers offering a wide range of properties, and their fundamental understanding requires their investigations by various techniques. One of them is transition metal (TM) K-edge X-ray Magnetic Circular Dichroism (XMCD), which is element selective, bulk sensitive and compatible with a wide range of experimental conditions. This short review presents the reciprocal investigation of PBA with TM K-edge XMCD, from the first studies demonstrating that qualitative local magnetic information could be obtained on PBA from TM K-edge XMCD until our on-going project aiming at fundamentally understanding TM K-edge XMCD thanks to PBAs as model-compounds.